Comparative analysis of steel structures stationary conveyors with hanging belt - Boslovyak P.V.; Zueva E.P. (Научно-технический вестник Брянского государственного университета)
Presents the results of computation of metal structures LLC «Сonveyor» with the subsequent analysis of its main struc-tural units. The analysis results of the metal structures, LLC «Сonveyor» with a similar metal structure obtained in the optimal design process.